(untitled) (Research, Society and Development, 2021)
Higher education in Nursing seeks to provide future professionals with general training, so that they can exercise critical-reflective thinking in the face of diverse and challenging everyday health situations, basing their conduct on ethical and bioethical principles. These changes reaffirm the need and duty of these institutions to train professional nurses trained to meet the expanded health needs of the population with an emphasis on the Unified Health System (SUS) and to ensure comprehensive care and the quality and humanization of care. It is an integrative review, with the objective of describing the challenges of nursing graduates in entering the job market. After associating all descriptors, 18 articles were selected. After the reflective reading, three categories emerged: Main concerns of the nursing graduate when entering the job market; Contributions of the nursing graduation formation process in its insertion in the job market; Nursing undergraduate training and impact on professional performance from the perspective of graduates. It is concluded that, from the construction of a reflective reading based on the theoretical articles used for the construction of this essay, it was evident in large parts of the studies used that the largest percentage of them envision, the commitment in the teaching-learning process as a great offender and contribute of the insecurity of this newly graduated nurse.